Dulung Proglacial Lake, Suru Sub-Basin, Western Himalaya: Evolution, Controls and Impacts on Glacier Stability - Garg, Siddhi; Garg, Purushottam Kumar; Yousuf, Bisma; Shukla, Aparna; Shukla, Uma Kant (Frontiers in Environmental Science, 2022)
Proglacial lakes are continually developing and expanding across the Himalayan glaciered terrain in response to climate change. These lakes are known to destabilize the glaciers by enhancing their frontal ablation, causing higher than average glacier area and mass losses. Thus, to comprehend the dynamics of proglacial lakes and their influence on the overall glacier health, we study the lake-terminating Dulung Glacier located in the Suru sub-basin, Ladakh, western Himalaya and compare it with the adjacent land-terminating Chilung Glacier. The pronounced melting of the Dulung Glacier, supported by glacier topography (surface gradient between accumulation and ablation zone) and valley morphology (wider near the snout and narrower downwards), seems to be the prime reason for the formation, accommodation and sustenance of the proglacial lake. The expansion in proglacial lake (0.008 km2a-1) during 1977-2018 is accompanied by an enhanced degeneration of the Dulung Glacier (mass balance: -0.47 ±0.06 m w.e.a-1, shrinkage rates: 0.3 ±0.001 %a-1; retreat rate: 32 ±0.7 ma-1, surface ice velocity reduction: 16%), which has accelerated post-1993. In comparison, land-terminating Chilung Glacier shows lower degeneration rates (mass balance: -0.28 ±0.02 m w.e.a-1; shrinkage: 0.2 ±0.001%a-1; retreat: 17 ±0.7 ma-1, surface ice velocity reduction: 8%) during 1971-2018. This suggests a substantial impact of the proglacial lake in enhancing the Dulung Glacier's sensitivity towards climate change compared to the Chilung Glacier. If the current rate of lake expansion continues, it would further enhance the Dulung Glaciers' degeneration rates, thus impacting its stability.